2014
DOI: 10.1080/02701367.2014.931203
|View full text |Cite
|
Sign up to set email alerts
|

The Pill Not Taken: Revisiting Physical Education Teacher Effectiveness in a Public Health Context

Abstract: In "Physical Education Teacher Effectiveness in a Public Health Context," we took a broad view of physical education (PE) teacher effectiveness that included public health need and support for PE. Public health officials have been consistent and fervent in their support of PE, and for more than two decades, they have called on schools to promote and provide physical activity. They have strongly recommended PE because: (a) It is part of the formalized school curriculum and an essential access point to provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 16 publications
2
54
0
4
Order By: Relevance
“…To support the development of objectively determined PA objectives, in tandem with achieving the multifaceted requirements of PE, it is essential that education makes a full contribution to these public health debates. Acknowledging that interventions within PE generate only small increases in PA,10 it is now time to look beyond PE as a ‘silver bullet’ for resolving the inactivity crisis, towards all segments of the school day. Importantly, what is at stake is not just achieving PA in PE, but encouraging lifelong participation in PA and the long-term health of children.…”
mentioning
confidence: 99%
“…To support the development of objectively determined PA objectives, in tandem with achieving the multifaceted requirements of PE, it is essential that education makes a full contribution to these public health debates. Acknowledging that interventions within PE generate only small increases in PA,10 it is now time to look beyond PE as a ‘silver bullet’ for resolving the inactivity crisis, towards all segments of the school day. Importantly, what is at stake is not just achieving PA in PE, but encouraging lifelong participation in PA and the long-term health of children.…”
mentioning
confidence: 99%
“…Thus, consistent with their peers in other countries, Finnish young people come close to, but do not reach, the target of half of PE lesson time spent in MVPA. Considering the suggestion by some scholars that PE should play a role in meeting daily PA recommendations for young people (McKenzie & Lounsbery, 2014;Pate et al, 2006;Sallis et al 2012), our study found that Finnish students gained an average of 28 minutes of MVPA per scheduled 90-minute PE lesson, equivalent to half of their recommended 60 minutes of MVPA for a given day. It seems, therefore, that PE lessons may only be an effective strategy to increase youth PA if the number of number of lessons per week is increased, as suggested by Racette et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among 15-year-old Finns, this proportion drops to just one tenth (Kokko & Hämylä, 2015). Young people spend a significant proportion of their waking hours in school and for this reason school is often identified as a key site in efforts to increase the daily physical activity levels of this population (McKenzie & Lounsbery, 2014;Pate et al, 2006;Sallis et al, 2012). Physical education (PE), in particular, is seen by some researchers as an untapped source of potential for young people's achievement of daily PA recommendations (McKenzie & Lounsbery, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Physical education carries the potential of promoting healthy and active lifestyles to students (McKenzie & Lounsbery, 2009); however, research has reported that current physical education programs in public schools often fail to achieve this objective (Chen, Zhu, Kim, Welk, & Lanningham-Foster, 2016; Rainer et al, 2012; Sun, Chen, & Zhu, 2012). Research also indicates factors including low social status (Hardman & Marshall, 2000; Macdonald, 1995; McKenzie & Lounsbery, 2009), limited instruction time (Locke, 1992; McKenzie & Lounsbery, 2009), limited decision making (Macdonald, 1995), lack of financial support (Hardman & Marshall, 2000; McKenzie & Lounsbery, 2009), lack of equipment and facilities (Fejgin, Ephraty, & Ben-Sira, 1995), lack of meaningful professional development (Armour & Yelling, 2004), challenging teacher socialization process (Templin & Richards, 2014), role limitation (Fejgin et al, 1995), students’ disruptive behaviors (Fejgin et al, 1995), and non-teaching related duties (Richards, Templin, Levesque-Bristol, & Blankenship, 2014) contribute to low quality physical education, as well as teachers’ low motivation and even teacher burnout.…”
Section: Introductionmentioning
confidence: 99%